Paper 21: Anterior Displacement of Tibial Spine Fractures, Does Anatomic Reduction Matter?. Issue 7 (30th July 2022) - Ganley, Theodore; Ellis, Henry; Shimberg, Jilan; Cruz, Aristides; Aoyama, Julien; Fabricant, Peter; Green, Daniel; Johnson, Benjamin; Kushare, Indranil; Lee, R. Jay; McKay, Scott; Milbrandt, Todd; et al.
Objectives: Operative treatment of displaced tibial spine fractures consists of suture or screw fixation to reduce the fragment in addition to restoring tension of the ACL. In some instances, the reduction is not anatomic, but it is unknown whether this impacts healing, range of motion, or laxity. The purpose of this study is to determine if residual displacement of the anterior portion of a tibial spine fragment affects the range of motion or laxity in post-operative and non-operatively treated tibial spine patients and to assess if anterior lip displacement (ALD) predicts complications in these patients. Methods: Data was gathered from an institutional review board-approved multicenter retrospective cohort of patients treated for tibial spine fractures between January 1, 2000, and January 31, 2019, at 10 institutions. Patients younger than 25 years of age with tibial spine fractures were included. Five-hundred seventy-eight patients were included in the cohort, excluding patients with missing data. Range of motion and ALD measurements were summarized and compared from pre-treatment to the patient's final visit. ALD measurements were categorized into four groups: 0 to <1 mm, excellent; 1 to <3 mm, good; 3 to 5mm, fair; and >5mm, poor. Results: Eighty-two percent (474/578) of patients had an operative treatment while only 18% of patients (104/578) had a non-operative treatment. There was a higher proportion of patients who had a positive Lachman test in the non-operative group (12%; 12/104) compared to the operative group (4%; 18/474; p=0.001). The surgical group had a median time of 3.4 months from surgery (range, 0.10 to 91.86 months) to final displacement measurement, while the non-operative group had a median time of 2.6 months from initial treatment to final displacement measurement (range, 0.07 to 61.37 months). Overall, there was no significant difference in the final range of motion measurements between these groups. The median anterior lip displacement measurement prior to treatment was 6.1mm and decreased to 0.7mm after treatment (p<0.001). At the final visit for patients, over half (52%; 248/477) were categorized in the excellent group for the anterior lip displacement measurement compared to only 4% (18/434) pre-treatment. Total range of motion prior to treatment was 75 degrees and it increased to 140 degrees after treatment (p<0.001). Patients categorized as having a fair final anterior lip displacement measurement had a 9.3 degree decrease in their final range of motion compared to patients categorized in the excellent group (β=-9.3; 95% CI=-13.77, -4.75; p<0.001). Patients categorized as having a poor final anterior lip displacement measurement had a 10.9 degree decrease in their final range of motion compared to patients categorized in the excellent group (β=-10.9; 95% CI=-18.26, -3.47; p=0.004). There were no associations detected between final anterior lip displacement category and laxity. Focusing on the operative group, there were no significant differences detected in laxity among the four different final anterior lip measurements (p=0.76). Post-hoc tests determined that the median total range of motion was larger for the excellent group (140 degrees) compared to the fair group (132.5 degrees; p<0.001). Similarly, there were significant differences detected between the excellent and fair group for flexion and extension measurements (p<0.001 and p=0.001, respectively). Eighteen patients (one non-operative) required reoperation for arthrofibrosis. Nine patients, one originally non-operative, had an ipsilateral ACL injury. Seven of these patients required ACL reconstruction. Operative patients who had both an extension and flexion contracture had 2.2 times the odds of having a complication compared to patients who did not have any contractures, this was independent of final ALD. Conclusions: Operative patients demonstrated greater ACL stability than the non-operative group, but had more complications and reoperations, independent from ALD. While ALD measurements of 'fair', 'good', and 'poor' all resulted in some loss of range of motion, this was of minimal clinical significance in patients at final follow up, suggesting that anatomic reduction may not be mandatory. UPLOAD-https://planion-client-files.s3.amazonaws.com/AOSSM/blobs/2f636269-0d58-4854-8d4a-568086ef7844/1/AOSSM_Table_Yen.docx